Feijão guandu para uso alimentar: composição química, funcionalidade e aspectos nutricionais - Tozo, Marcelo Larsen de Lima (2025)
This dissertation aims to develop and apply analytical procedures to evaluate the total levels, bioaccessibility, and bioavailability of essential elements and total proteins in two pigeon pea (Cajanus cajan (L.) Millsp) varieties previously selected for human consumption. Raw and cooked samples were evaluated at different stages of maturation, as well as commercial varieties of common beans (carioca and black). Bioaccessibility and bioavailability were obtained after in vitro gastrointestinal digestion simulations and bioassays with Caco-2 cells. For proteins, the total fraction and the bioaccessible fraction were quantified by combustion (Dumas), and free amino acids by high-performance liquid chromatography (HPLC). The macro and micronutrients evaluated, Ca, Mg, P, Cu, Fe, and Zn, were determined by inductively coupled plasma optical emission spectrometry and mass spectrometry (ICP OES and ICP-MS), after microwave-assisted decomposition using diluted acid (7.0 mol L-1), both for total contents and for bioaccessible and bioavailable fractions. The bioaccessibility of elements varied from 0.8 to 19% for Ca and from 48 to 67% for Cu. Bioaccessibility of Ca, Fe, Mg, and Zn decreased with bean maturation. Finally, an in vitro intestinal simulation with Caco-2 cells, aimed at estimating nutrient bioavailability, faced issues with the integrity of the cell monolayer, making it impossible to estimate bioavailability values. However, the results obtained suggest the direction to be followed for improving this experiment and obtaining reliable results. Regarding crude protein content, pigeon pea samples were close to 20%. For amino acids, amounts ≥ 1% of glutamic acid, aspartic acid, and leucine were found. For the mature grain, lysine and phenylalanine were present in amounts ≥ 1%, compared to the green grain. However, in the mature grain, the amounts of glycine, histidine, threonine, alanine, and tyrosine were low (≤ 0.4%), and no methionine, cystine, or taurine were detected in either grain. The protein bioaccessibility varied between 16.4% and 19.4%. There was an increase in the total protein content with the maturation of the beans, while the bioaccessible percentage remained unchanged. For the recommended daily intake (RDI), the consumption of 100 g of cooked food suggests that the pigeon pea may be an alternative source of nutrients, highlighting Mg and P, although its contribution is lower compared to the commercial varieties of carioca and black beans. Additionally, all the beans studied show potential for protein supplementation, ranging from 32.8 – 38.8% of the RDI, reinforcing the importance of these legumes and others in human nutrition.This study is significant from a nutritional perspective, providing unprecedented data on the nutritional aspects of two varieties of pigeon peas and the bioaccessibility of essential elements, indicating their use as a consumption alternative.